Current trends in non–HDL cholesterol and LDL cholesterol levels in adults with atherosclerotic cardiovascular disease - Vega, Gloria Lena; Grundy, Scott M. (Journal of clinical lipidology, 2019)
Low-density lipoprotein cholesterol (LDL-C) and non–high-density lipoprotein cholesterol (non–HDL-C) are targets for prevention of atherosclerotic cardiovascular disease (ASCVD). The American Heart Association and American College of Cardiology recently modified recommendations for clinical management of cholesterol in secondary and primary prevention. Accordingly, the present article examines the need for cholesterol-lowering drugs in the U.S. population with ASCVD. This study examines trends in non–HDL-C and LDL-C levels in a free living population of ASCVD subjects between 1999 and 2016. National Health and Nutrition Examination Surveys database included 4920 adults with ASCVD aged 40 to 85 years. Complete data were available for 4226. Trend analysis of changes in lipids is shown in box plots. Mean age was 67 years with 57% males. Over 17 years, LDL-C decreased significantly by 24% and non–HDL-C by 21%. Over the period of study, reported intake of cholesterol-lowering drugs rose from 37% in 1999-2000 to 69% in 2015 to 2016. Over this same period, serum triglycerides decreased by 29% (P < .001) and HDL-C rose by 6%. The changes in LDL-C and non–HDL-C in patients with ASCVD over a 17-year period probably are related to increased treatment with statins. However, the changes are too small to be explained by widespread use of high-intensity statins, which is the current recommendation for patients with ASCVD. These findings pose a challenge for professional education to support implementation of current guidelines for cholesterol-lowering therapies. •Trends in non–high-density lipoprotein and low-density lipoprotein levels were tracked for 17 years in subjects with atherosclerotic cardiovascular disease.•Non–high-density lipoprotein and low-density lipoprotein cholesterol decreased by 21% and 24%, respectively.•Intake of cholesterol-lowering drugs increased from 37% to 69% over 17 years.•New treatment strategies of patients with atherosclerotic cardiovascular disease are needed to optimize risk reduction.